The tragedy of Antony and Cleopatra - Zak, William F. (Lexington Books, 2015)
The immortal worm: Caesar Augustus – A wounded chance: Marc Antony – An honoured gash: Cleopatra
Includes bibliographical references and index
Keywords: Antonius; Marcus; Cleopatra; Antony and Cleopatra; Shakespeare; William